New optical solitons for Biswas-Arshed equation with higher order dispersions and full nonlinearity - Korpinar, Zeliha; İnç, Mustafa; Bayram, Mustafa; Hashemi, Mir Sajjad (Elsevier Gmbh, 2020)
In this paper, the extended Jacobi's elliptic function approach is used to solve the Biswas-Arshed equation in two different types. This method reveals several optical solitons including traveling wave solutions. The found solutions are identified bright, dark, singular optical solitons and Jacobi elliptic function solutions. Reliability of the process is presented with graphical consequence of derived solutions.
Keywords: Optical solitons; Traveling wave solutions; Biswas-Arshed equation; Jacobi's elliptic function